Analisis Mekanisme Penetapan Harga dalam Perspektif Etika Ekonomi Islam Menurut Pemikiran Imam Al-Ghazali - Muhammad Rohid; Ahmad Fauzi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to examine one of the disciplines of Islamic law, namely the pricing mechanism from the perspective of Imam Al-Ghazali, in order to create a healthy market environment free from monopolistic practices and manipulation, and aligned with Sharia principles. This research employs a descriptive qualitative approach using a literature study method by reviewing various relevant books, classical texts, articles, and academic journals related to Islamic economics and Imam Al-Ghazali’s thought. The findings indicate that the concept of fair pricing is not solely dependent on the interaction between supply and demand, but must also consider moral and social dimensions, such as justice, honesty, and public welfare. Imam Al-Ghazali strongly emphasized that economic transactions should uphold ethical standards and social responsibility to prevent exploitation and inequality. He argued that pricing must reflect not only market dynamics but also the broader ethical framework rooted in Islamic values. Furthermore, the study explores the concept of economic equilibrium in relation to pricing mechanisms, where prices should ideally balance individual interests with communal welfare. The research also discusses the correlation between economic balance and price-setting policies, including the views of other classical and contemporary Islamic scholars. It is found that state intervention is permissible in certain conditions—particularly when market mechanisms fail to ensure fairness—thus justifying government roles in market supervision and price stabilization. One of the key concepts in Islamic economics is the notion of a just price (al-thaman al-‘adl), as emphasized by Imam Al-Ghazali.. This study concludes that understanding pricing from Al-Ghazali’s perspective offers valuable insights for building ethical and socially responsible economic systems aligned with Islamic teachings.